2020
DOI: 10.7193/dm.098.37.63
|View full text |Cite
|
Sign up to set email alerts
|

Améliorer l’attitude et l’intention de vaccination : le cas du rappel du vaccin Diphtérie-Tétanos-Poliomyélite (DTP)

Abstract: Entre 18 et 25 ans, les jeunes adultes doivent prendre pour la première fois la décision de se faire vacciner (rappel du vaccin DTP). Adoptant une démarche expérimentale, cette étude menée auprès de 303 jeunes adultes teste l’efficacité de 6 combinaisons de messages pro-vaccination DTP sur les changements d’attitude et d’intentions comportementales, en faisant varier le cadrage (gain vs. perte) et l’argument utilisé (se faire vacciner pour soi, pour les autres, ou pour respecter la loi). Les résultats montrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Some participants may not have paid sufficient attention to the information disseminated in the awareness campaign. In 2020, Plichon et al studied the impact of the framing of a message and the arguments presented to explain changes in attitude towards vaccinations, intention to be vaccinated or to recommend a vaccination to relatives [ 16 ]. Their study was carried out with young adults aged 18 to 25 years and showed that the formulation of a message from a punitive point-of-view (non-vaccination is illegal) did not increase the intention of participants wanting to be vaccinated, whereas a positive message formulation (being vaccinated respects the law) led to a feeling of being protected by the law and a positive change was reported in the attitude towards vaccination as well as stronger intention for participants to be vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…Some participants may not have paid sufficient attention to the information disseminated in the awareness campaign. In 2020, Plichon et al studied the impact of the framing of a message and the arguments presented to explain changes in attitude towards vaccinations, intention to be vaccinated or to recommend a vaccination to relatives [ 16 ]. Their study was carried out with young adults aged 18 to 25 years and showed that the formulation of a message from a punitive point-of-view (non-vaccination is illegal) did not increase the intention of participants wanting to be vaccinated, whereas a positive message formulation (being vaccinated respects the law) led to a feeling of being protected by the law and a positive change was reported in the attitude towards vaccination as well as stronger intention for participants to be vaccinated.…”
Section: Discussionmentioning
confidence: 99%